Building trust and equity in vaccine communication through community engagement - Theresa Sommers; Meredith Dockery; Nina Burke; Sharin D’Souza; Brittany Troupe; Tina Agbonyinma; Harikeerthan Raghuram; Kathryn L. Hopkins; Elizabeth Kohlway; Pedja Stojicic; Anant Bhan (Human Vaccines & Immunotherapeutics)
That the COVID-19 pandemic has exacerbated inequities in health has been well studied in recent years, yet the ways in which the pandemic has also revealed existing inequities in communication, specifically health communication, is less well understood. Communities experience differing levels of basic literacy, health literacy, and access to information, as well as differing levels of trust in public health programs. Community engagement (CE) strategies are critical to support improved communication, trust, and equity in vaccination programs. This paper shares two real-world examples of impactful CE strategies from community-based programming to explore how well-designed community engagement strategies can support improved communication, trust, and equity in vaccination programming. Lessons learned from these programs highlight that vaccine communication programs should continuously engage communities to amplify community perspectives and voices to ensure sustained vaccine demand and uptake.